Isomorphisms and Automorphisms Groups: An exploration of isomorphisms and automorphisms in group theory (Journal of Advances and Scholarly Researches in Allied Education, 2015)
We shall study the concepts of isomorphism and automorphism of group. We shall also discuss inner automorphisms. Before this topic, firstly we discuss about group, subgroup, normal subgroups. An isomorphism could also be termed as an “indirect” equality in algebraic systems. An isomorphism of a group G to itself is called automorphism. We discuss about the theorem whose state that let G be a group and let Aut (G) de not the set of all automorphism of a group G . Then Aut (G) forms a group under the composition of mapping as binary operation. After that we solve the problem and example related to this topic.